2020
DOI: 10.3892/ijmm.2020.4590
|View full text |Cite
|
Sign up to set email alerts
|

A risk score system based on DNA methylation levels and a nomogram survival model for lung squamous cell carcinoma

Abstract: Lung squamous cell carcinoma (LScc) is one of the primary types of non-small cell lung carcinoma, and patients with recurrent LScc usually have a poor prognosis. The present study was conducted to build a risk score (RS) system for LScc. Methylation data on LScc (training set) and on head and neck squamous cell carcinoma (validation set 2) were obtained from The cancer Genome Atlas database, and GSE39279 (validation set 1) was retrieved from the Gene Expression Omnibus database. differentially methylated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Based on the expression profiling of the TCGA dataset, the Pearson correlation coefficients between redox-related protein-coding genes and all lncRNAs were calculated by the built-in function ‘cor.test’ in R [ 20 ]. Subsequently, lncRNAs with |correlation coefficients| >0.4 and p values <0.001 were considered as redox-related lncRNAs for further analysis [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the expression profiling of the TCGA dataset, the Pearson correlation coefficients between redox-related protein-coding genes and all lncRNAs were calculated by the built-in function ‘cor.test’ in R [ 20 ]. Subsequently, lncRNAs with |correlation coefficients| >0.4 and p values <0.001 were considered as redox-related lncRNAs for further analysis [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…We used cor.test function to detect the relationships between lncRNAs (Zhang et al, 2020a). Then, we evaluated the accuracy of the risk model using univariate, multivariate, and receiver operating characteristic (ROC) curves.…”
Section: Risk Model Assessmentmentioning
confidence: 99%
“…ABAT was related to the prognosis of patients with liver cancer, pancreatic cancer, and breast cancer [ 14 , 15 , 36 ]. SLC25A42, AMT, and IVD genes have also been found in other prognostic models of lung cancer [ 37 , 38 ]. However, no studies have found a relationship between AMT and cancers.…”
Section: Discussionmentioning
confidence: 99%